Epigallocatechin gallate hinders human hepatoma and colon cancer sphere formation. Issue 1 (January 2016) - Wubetu, Gizachew Y; Shimada, Mitsuo; Morine, Yuji; Ikemoto, Tetsuya; Ishikawa, Daichi; Iwahashi, Shuichi; Yamada, Shinichiro; Saito, Yu; Arakawa, Yusuke; Imura, Satoru
Abstract: Background and Aim: The long‐term survival of patients with hepatocellular carcinoma remains unsatisfactory because of the presence of cancer stem cells (CSCs), which are responsible for tumor recurrence and chemoresistance after hepatectomy. Drugs that selectively target CSCs thus offer great promise for cancer treatment. Although the antitumor effects of epigallocatechin gallate (EGCG) have been reported in some cancer cells, its effects on CSCs remain poorly studied. In this study, we investigated the effects of EGCG on human hepatoma and colon CSCs. Methods: HepG2 and HCT‐116 cell lines were enriched by sphere formation, and their gene‐expression profiles were analyzed by quantitative real‐time polymerase chain reaction. EGCG‐induced growth inhibition in the parental cells was determined by WST‐8 assay, and protein expression was assessed by western blotting. Cell cycle profile and apoptosis analysis was performed using flow cytometer. Results: Sphere‐derived cells grown in serum‐free, nonadherent cultures showed increased expression of stem cell markers, Nek2, and ATP‐binding cassette transporter genes, compared with parental cells grown in conventional culture. EGCG induced growth inhibition in the parental cells in a dose‐dependent manner. EGCG also inhibited self‐renewal in hepatoma and colon CSCs, attenuated the expression of stem cell markers and ATP‐binding cassette transporter genes, which are putative molecules associated with treatment resistance in CSCs, and decreased the transcription of Nek2 and p‐Akt, resulting in the inhibition of Akt signaling. EGCG also altered cell cycle profile and apoptosis, which may in part play an important role in EGCG‐induced cancer cell death. Conclusions: Overall, these results suggest that EGCG could be a useful chemopreventive agent for targeting hepatocellular carcinoma and colon CSCs, in combination with standard chemotherapies.